Museums Tour Enhancement With Augmented Reality: A Proposed Enhancement Designs of Exhibits to Improve Informal Learning - Mohammed Daud, Danial Hariz (Universiti Teknologi PETRONAS, 2020)
Augmented Reality (AR) is one of the fastest growing fields in computing and it has penetrated into many other areas such as medical, engineering, and education. In this paper, we will investigate and propose a design to develop an interactive museum experience with AR to make it engaging for museum visitors and improve their retention towards museum exhibits. The implementation of AR may also yield unexpected benefits, such as providing users new perspective with non-linear interactivity, as well as encouraging them to experiment with technology and increase their curiosity. Benefits such as these may have the potential to better enhance the chances for learning and analytical activities to take place.